IFPRI Malawi maize market report, December 2025 - International Food Policy Research Institute; Benson, Anderson (International Food Policy Research Institute, 2026)
Retail prices of maize remained unusually stabile in December, when prices typically rise. Retail prices were stabilized by sustained informal imports at stable prices.